Community Satisfaction Index with Development Results of The Banten Province PUPR Service For Development Work Area II (Serang City, Serang District And Cilegon City) 2024 - Karvina Budiwati Apriliani; Arlan Marzan; Isvan Taufik; Resti Meliana Sari; Natta Sanjaya; Siti Yuniar (Indonesian Journal of Social Science Research, 2025)
Infrastructure such as roads, bridges, irrigation, public facilities, and access to clean water not only improves connectivity but also accelerates the flow of goods and services, increases accessibility, and encourages equitable development between regions. This activity (study) aims to measure the level of community satisfaction as service users and improve the quality of infrastructure development in Development Work Area (WKP) II (Serang City, Serang Regency and Cilegon City). The research approach used was quantitative descriptive analysis, data collection techniques used were interviews, observation, documentation and literature study. The research population is all people who use the Banten Province PUPR Service infrastructure in the Development Work Area (WKP) II. The sampling technique used was the lemeshow formula with a sample size of 267 respondents. The data analysis technique was the calculation of the infrastructure service satisfaction index (IKLI). The research results show that the infrastructure service quality index value for Banten province in 2024 is 2.86 with the performance of service units being satisfied. This shows that the people of Banten province feel the results of the development of the Banten Province PUPR service, especially infra structure services, are satisfied.